2004
DOI: 10.1055/s-2004-829110
|View full text |Cite
|
Sign up to set email alerts
|

The Regioexhaustive Functionalization of Difluorophenols and Trifluoro­phenols Through Organometallic Intermediates

Abstract: 2, 2, 2, 3, 3, 2,4,5-trifluorophenol and 2,3,4-trifluorophenol were converted into all 18 possible di-or trifluorinated hydroxybenzoic acids (1a-c, 4a-c, 9a-c, 12a,b, 14a-c, 17a,b, 18a,b), all of them new compounds. The phenolic hydrogen atom was replaced by a methoxymethyl or, less frequently, by a triisopropylsilyl group, which exerted an ortho activating or ortho shielding effect, respectively. Sites flanked by two electronegative substituents (fluorine, alkoxy) were deprotonated with particular ease. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Ultimately, we focused our research on the generation of the ortho -fluorinated aryllithium amides at low temperature. We found that a regioselective ortho- deprotonation using LiTMP, followed by trapping with triisopropyl borate provided >99% of fluoro-arylboronic acid 14 after an acidic quench.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, we focused our research on the generation of the ortho -fluorinated aryllithium amides at low temperature. We found that a regioselective ortho- deprotonation using LiTMP, followed by trapping with triisopropyl borate provided >99% of fluoro-arylboronic acid 14 after an acidic quench.…”
Section: Resultsmentioning
confidence: 99%